12‐3: A Highly Mass‐producible Nano‐lens Array Technology for Optically Efficient Full‐color Organic Light Emitting Diode Display Applications. Issue 1 (29th May 2019) - Park, Young-Sam; Han, Kyung-Hoon; Cho, Doo-Hee; Cho, Nam Sung; Han, Yoonjay; Lee, Jonghee; Lee, Hyunkoo; Yu, Byounggon; Lee, Jeong-Ik; Kim, Jang-Joo
Abstract : Recently, we have reported that a nano‐lens array (NLA) technology using a very simple and fab‐compatible vacuum deposition process contributes to highly efficient and color stable green and blue organic light emitting diodes (OLEDs). Here, the technique is applied to red OLEDs. With NLA, the increase ratio of current efficiency is about 1.57 which is similar to those of green and blue OLEDs (1.56, 1.59). Furthermore, color coordinate change measurement values of red OLEDs in a wide viewing angle ranging from 0° to 60° are reduced as green and blue OLEDs do, indicating that NLA has a great potential for the development of the optically efficient full‐color OLED displays composed of three color OLED pixels.